2016
DOI: 10.4103/2230-8210.176343
|View full text |Cite
|
Sign up to set email alerts
|

Postural variation of pulmonary diffusing capacity as a marker of lung microangiopathy in Indian patients with type 2 diabetes mellitus

Abstract: Introduction:Diabetes mellitus (DM) is characterized by the presence of chronic hyperglycemia and formation of advanced glycation end products (AGEs). Interaction between AGE and its receptor leads to endothelial damage and microangiopathy. This study was undertaken to investigate the possibility of using a postural variation of diffusing capacity as an early marker of lung microangiopathy and its correlation with the level of adhesion molecules, HbA1c, duration of diabetes, and insulin resistance in type 2 DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Diffusion capacity of the lungs for carbon monoxide is a sensitive measure of pulmonary diffusion capacity and commonly applied to assess the function of the transfer of gas across the respiratory membrane between the alveoli and capillaries of the lungs [ 35 , 36 ]. It is reported that DLCO in patient with T2DM is significantly impaired, which is likely associated with the thickening of the gas exchange membrane of the lungs [ 6 ], resulting from chronic hyperglycemia [ 37 , 38 ], dyslipidemia and insulin resistance [ 39 ]. Possible pathological processes associated with impaired pulmonary function in T2DM may include non-enzymatic glycosylation of lung elastin structures, which could stiff the lung [ 40 ] and cause a restrictive impact on ventilation; and diabetes-induced microvascular complications, which could impair the diffusion [ 37 , 41 ] and diminish gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion capacity of the lungs for carbon monoxide is a sensitive measure of pulmonary diffusion capacity and commonly applied to assess the function of the transfer of gas across the respiratory membrane between the alveoli and capillaries of the lungs [ 35 , 36 ]. It is reported that DLCO in patient with T2DM is significantly impaired, which is likely associated with the thickening of the gas exchange membrane of the lungs [ 6 ], resulting from chronic hyperglycemia [ 37 , 38 ], dyslipidemia and insulin resistance [ 39 ]. Possible pathological processes associated with impaired pulmonary function in T2DM may include non-enzymatic glycosylation of lung elastin structures, which could stiff the lung [ 40 ] and cause a restrictive impact on ventilation; and diabetes-induced microvascular complications, which could impair the diffusion [ 37 , 41 ] and diminish gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that DLCO in patient with T2DM is significantly impaired, which is likely associated with the thickening of the gas exchange membrane of the lungs [6], resulting from chronic hyperglycemia [37,38], dyslipidemia and insulin resistance [39]. Possible pathological processes associated with impaired pulmonary function in T2DM may include non-enzymatic glycosylation of lung elastin structures, which could stiff the lung [40] and cause a restrictive impact on ventilation; and diabetes-induced microvascular complications, which could impair the diffusion [37,41] and diminish gas exchange. It is reported that lung function assessed by forced vital capacity and forced expiratory volume in 1 sec (FEV-1) are inversely correlated with HbA1c [42][43][44] and DLCO is significantly impaired in patients with T2DM [44].…”
Section: Taichi Improved Pulmonary Diffusion Capacity In T2dmmentioning
confidence: 99%
“…These patients were at high risk for the relatively rapid deterioration of kidney function [ 27 ]. DM can cause damage to the pulmonary vascular endothelium and decrease the release of vasodilators, thus aggravating the degree of atherosclerosis, further increasing blood pressure, and eventually leading to high pressure load in the right ventricle and increased pulmonary vascular resistance, resulting in PAH [ 28 , 29 ]. Agarwal R et al found that ambulatory systolic blood pressure (BP) was strongly associated with the progression of chronic kidney disease (CKD) and was an independent predictor of ESRD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in DM, there are two tissue specific paradoxical events in the vasculature with excessive formation of premature blood vessels afflicting the retina, while deficiency of small blood vessels in the skin, contributes to impaired wound healing [6]. Hence, the use of angiogenic inhibitors is a common treatment modality for diabetic retinopathy [27, 28]. Similarly, abnormal angiogenesis and vascular dysfunction are also prominent features of active TB and utilization of host-directed therapies aimed at inhibition of these pathways has been proposed as an adjunct measure for TB treatment [16, 17].…”
Section: Discussionmentioning
confidence: 99%